Perancangan Video Dokumenter Semanggi Suroboyo Sebagai Hidangan Unik Khas Surabaya: Design of Documentary Video of Semanggi Suroboyo - Zaky, Raden; Setiawan, Bayu Setiawan; Diana Aqidatun Nisa, Diana Aqidatun Nisa (Jurnal Desain Komunikasi Visual Asia, 2025)
Semanggi Suroboyo is one of Surabaya's culinary specialties that has begun to be marginalized due to modernization and changes in people's preferences, especially among Generation Z. The lack of promotion and lack of understanding of the history and cultural values ​​contained in this dish has accelerated the loss of Semanggi Suroboyo's existence. Therefore, this study aims to design a documentary video that is not only informative, but also carries a more dynamic, interesting, and easily accepted storytelling by Generation Z. With a more engaging cinematic approach and the use of a strong Call to Action (CTA), this video is expected to be able to rebuild public interest in Semanggi Suroboyo and change the stereotype that traditional food is something old-fashioned and less relevant in the modern era. The design method involves in-depth research through observation, interviews, and literature studies related to culinary and visual media. The results of this design are expected to be an effective solution in reintroducing Semanggi Suroboyo to the younger generation and encouraging efforts to preserve Surabaya's culinary specialties through more adaptive and interactive digital media.